Speech therapist knowledge and action in intrafamiliar violence situations against children and teenagers (Research, Society and Development, 2022)
Objective: Analyse the speech therapists knowledge about the intrafamiliar violence against children and teenagers and understand how they act in these cases. Method: Is is about a transversal study, ocurred from the sendig of questionnaires to 4.297 speech therapists, registered on CREFONO-3. The data obtained were explored through the content analysis. Results: Of the 75 participator speech therapists, 39 (52%) took care of children and/or teenagers with violence suspicion or confirmation. The most attacked public were children, between 2 to 12 years. The most quoted violence kind were, psychological and physical. The most found speech therapy alteration in the victims was the language development delay. Concerning the speech therapist self understanding about its knowledge about violence, 57,5% signalized detain knowledge. About the ability to identify to take care or follow intrafamiliar violence cases against children and/or teenagers, 65,3% of the speech therapists described themselves how capable and 34,7% don’t feel themselves prepared. Conclusion: The speech therapist knowledge about intrafamiliar violence against children and teenagers its faced to violence kinds, identification type, case notification, welcome procedures and conduction, connection between speech therapy sign and the violence and professional disorganization to deal with these situations. Then the speech therapist action occur through the cases notification, relatives conversation, conductions and/or contact with other professionals.